0708 The Role of Combined Subjective Sleep Quality and Objective Sleep Efficiency Variability in Frailty Status. (12th April 2019) - Alshehri, Mohammed; Alenazi, Aqeel; Alqahtani, Bader; Perlis, Michael; Professor, Associate
Abstract: Introduction: Frailty is prevalent in older adults and associated with common risk factors related to mortality. Previous studies showed an association between sleep disturbances and frailty in older adults; however, this association might not be presented by the discrepancy between subjective and objective measures of sleep. Thus, this study aimed to investigate the impact of combined perceived sleep quality (SQ) and objective sleep efficiency (SE) variability on the frailty status. Methods: Data from Midlife in the United States for 108 individuals aged between 65-85 years was utilized. Participants were grouped into four categories based on Pittsburgh Sleep Quality Index and Coefficient of Variance (CV) of 7 nights of ActivWatch measure for SE. The median of CV for SE was chosen as a cutoff score for low and high sleep variability. The sample was divided into: Good Sleep Quality Low Sleep Variability (GSLV), Poor Sleep Quality Low Sleep Variability (PSLV), Good Sleep Quality High Sleep Variability (GSHV), and Poor Sleep Quality High Sleep Variability (PSHV). Frailty status was measured including low physical activity, exhaustion, weight loss, slow gait speed and muscle weakness. A multinomial regression analysis was used to determine the strength of association between groups to predict the frailty status at 0.05 significant level. Results: A total of 29 participants in GSLV group, 26 participants in PSLV group, 24 in GSHV group, and 29 in PSHV group. People in the PSHV group were most likely to have frailty (odds ratio =7.42; 95% confidence interval = [1.03, 53.17], p=0.046) after controlling for age, gender and Waist-Hip ratio. No significant associations were found after separating the subjective measure and objective measure. Conclusion: People with poor SQ and high SE variability were about seven times more likely to be a frail compared to other groups. The finding suggests the need to assess both subjective and objective sleep of several nights for older adults. A prospective longitudinal study with larger sample size is needed to confirm such relationship. Support (If Any): N/A